2010
DOI: 10.1007/s12272-010-1120-6
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane suppresses TARC/CCL17 and MDC/CCL22 expression through heme oxygenase-1 and NF-κB in human keratinocytes

Abstract: Sulforaphane (4-methylsulfinylbutyl isothiocyanate, SFN) from broccoli has been used a chemopreventive photochemical as detoxification of xenobiotics and anti-inflammatory, however, there is no studies for Th2 chemokine expression through heme oxygenase-1 and NF-κB in keratinocytes. Atopic dermatitis is a chronically relapsing pruritic inflammatory skin disease. SFN is demonstrated to have anti-inflammatory and anti-oxidant effects. This study aimed to define whether and how SFN regulates Th2-related chemokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…Studies have indicated that NF-κB induces expression of HO-1 in tumor tissues [28][31]. Moreover, numerous studies suggested a direct relationship between NF-κB and HO-1, but the function of NF-κB in regulating HO-1 expression in human cells is controversial [32][35]. In this study, our data showed that hypoxia induces Prx1 and NF-κB, and Prx1 regulates HO-1 via activating NF-κB.…”
Section: Discussionsupporting
confidence: 47%
“…Studies have indicated that NF-κB induces expression of HO-1 in tumor tissues [28][31]. Moreover, numerous studies suggested a direct relationship between NF-κB and HO-1, but the function of NF-κB in regulating HO-1 expression in human cells is controversial [32][35]. In this study, our data showed that hypoxia induces Prx1 and NF-κB, and Prx1 regulates HO-1 via activating NF-κB.…”
Section: Discussionsupporting
confidence: 47%
“…Some reports show that compounds or extract from natural product decrease the MDC production via inhibition of NF-κB and STAT1 activation. 33,34) Even though STAT1 and NF-κB signal were activated by IFN-γ and TNF-α in our condition, J7 only inhibited the activation of STAT1 signal. In RAW264.7 macrophages, J7 also inhibited the STAT1 activation, but not NF-κB, by LPS stimulation (Fig.…”
Section: Resultsmentioning
confidence: 69%
“…23,24) Furthermore, several plant extracts and compounds have been shown to inhibit the actions of inflammatory chemokines via the regulation of signaling pathways stimulated by IFN-γ and TNF-α, including STAT1, NF-κB, and mitogen-activated protein kinase (MAPK) cascades. [25][26][27][28] Among these transcription factors, the STAT1 protein is a crucial and specific regulator of IFN-γ-induced signals that controls the transcription of target genes, including MDC. 23,29) Therefore, we tested the effect of J7 on the activation of STAT1 in IFN-γ-and TNF-α-treated HaCaT keratinocytes and detected a high level of phosphorylated STAT1 at 15 min after cytokine treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, our results showed that keratinocytes express more CCL17 and CCL22 on TWEAK stimulation. CCL17 and CCL21 can be secreted by keratinocytes (36) and also contribute to the local recruitment of macrophages (37). The expression levels of CCL17 and CCL22 correlates with CCL19 in inflamed lungs, which further leads to the accumulation of macrophages (38).…”
Section: Discussionmentioning
confidence: 99%